A Review on Role of miRNA in Kidney Diseases - Priyadarshini . (Journal of Global Pharma Technology, 2017)
micro RNA or miRNA are short non-coding RNAs species that inhibit target gene expression by blockingprotein translation or by mRNA degradation. Several studies have shown that miRNAs regulatethousands of gene expressions throughout the genomic machinery and play important roles in thephysiological and pathological events. In addition, miRNA play important role in pathogenesis of variousrenal diseases, including diabetic nephropathy, renal carcinoma, polycystic kidney diseases, allograftrejection etc. miRNA as a biomarker has been an area of intensive researches, as it has been discoveredto be potential therapeutic tools to manage several diseases. Therapeutic potential of miRNA-basedtreatment though promising but various challenges such as target specificity is still to be explored.Identification of miRNA and their target can provide a novel therapeutic candidate for curing variouskidney diseases. In this review, we have stated the role of various miRNAs in the development of variousrenaldiseases.